Aktivitas Ramuan Herbal sebagai Antagonis Reseptor H1, Relaksan Otot Polos dan Penghambat Degranulasi Sel Mast sebagai Antiasmatik - Ratnawati, Galuh; Damayanti, Kiki; Nugroho, Agung Endro (Jurnal Kefarmasian Indonesia, 2022)
Asthma is still become a major health problem worldwide, affected all ages from pediatrics to adults. The severity of the disease vary from mild to severe and leads to the risk of death. The uses of medicinal plants as antiasthmatic have often been conducted by the local community. The present study was conducted in vitro and in vivo to determine the activities of herbs containing of sembung leaves (Blumea balsamifera L.), kemukus seeds (Piper cubeba L.), teki rhizome (Cyperus rotundus L.), and patikan kebo herbs (Euphorbia hirta L.) with certain ratio as an antiasthmatic. The in vitro test was carried out on isolated smooth muscle cells of guinea pig. Histamine was used to stimulate the contraction of smooth muscle cells of guinea pig trachea. The in vivo test was carried out using guinea pigs which sensitized with ovalbumin and administered with the herbs formula. The trachea of guinea pigs were prepared for histopathological examination and stained on toluidine blue. The result revealed that the antiasthmatic herbs of 1, 2, and 3 showed activities as H1 receptor antagonists. The antiasthmatic herbs of 1, 2, and 3 were able to relax the smooth muscle of guinea pig’s trachea that was experiencing contraction, but in lower level compared to theophylline. The antiasthmatic herbs formula in this study did not have the activity to inhibit mast cell degranulation.